Peran Baitul Mall Wat Tamwil (BMT) UGT Nusantara Capem Muncar dalam Keberhasilan Usaha Mikro Kecil Menengah di Desa Tembokrejo - Noviansyah, Rizki Alfin; Khoiruddin, Muh.; Habibulloh, Habibulloh (CV. Lentera Literasi Indonesia, 2025)
This study aims to identify and analyze the role of BMT UGT Nusantara Capem Muncar in supporting the success of Micro, Small, and Medium Enterprises (MSMEs) in Tembokrejo Village, Muncar District, Banyuwangi Regency. The research uses a qualitative approach with a field research design. Data collection techniques include observation, interviews, and documentation, with research subjects consisting of BMT management and MSME actors who are financing clients. The results show that BMT UGT Nusantara Capem Muncar plays a significant role in facilitating MSME capital through sharia-based financing products, particularly the modal usaha barokah (blessed business capital) financing. In addition, BMT provides business assistance, financial education, and easy access to inclusive financial services. The impact of this financing is evident in the increased income of business actors, expansion of business scale, creation of new jobs, and improved awareness of the importance of financial management. BMT UGT Nusantara Capem Muncar functions not only as a microfinance institution but also as a strategic partner in community economic empowerment and sustainable MSME development.